2021
DOI: 10.1038/s41598-021-00528-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in NDFIP1 modifies the metabolic patterns in immune cells of multiple sclerosis patients

Abstract: One of the 233 polymorphisms associated with multiple sclerosis (MS) susceptibility lies within the NDFIP1 gene, and it was previously identified as eQTL in healthy controls. NDFIP1 shows interesting immune functions and is involved in the development of the central nervous system. We aimed at studying the NDFIP1 variant on activation and metabolism of immune cells. NDFIP1 mRNA and protein expression were assessed in PBMCs by qPCR and western blot in 87 MS patients and 84 healthy controls genotyped for rs49126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Although the exact identity and functions of X-11,315 remain unclear at the current stage, this finding undoubtedly provides clues guiding future developments of metabolic biomarker-based diagnostic tests and therapies for RC. Similar mechanisms could be found in other diseases, such as asthma [48], multiple sclerosis [49], and so on. Deeper investigations into the interplay between AFF3 and metabolic networks could yield more fruitful outcomes moving forward.…”
Section: Discussionsupporting
confidence: 71%
“…Although the exact identity and functions of X-11,315 remain unclear at the current stage, this finding undoubtedly provides clues guiding future developments of metabolic biomarker-based diagnostic tests and therapies for RC. Similar mechanisms could be found in other diseases, such as asthma [48], multiple sclerosis [49], and so on. Deeper investigations into the interplay between AFF3 and metabolic networks could yield more fruitful outcomes moving forward.…”
Section: Discussionsupporting
confidence: 71%
“…The detected ROS increase could reflect the higher activation level of T cells typical of MS patients even without stimulus. A previous study demonstrated higher levels of CD69 in T cells from MS patients [ 6 ], which could be mediated, at least in part, by the increase of mitochondrial superoxide anion after PHA stimulation. Although this increase was observed in non-stimulated and PHA-stimulated cells, after being corrected by mitochondrial mass, only in the non-stimulated condition remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these studies are conducted at the central nervous system (CNS) level, some of them start to assess circulating immune cells. They describe the peripheral blood mononuclear cells (PBMCs) immunometabolic profile of MS patients associated with the progressive form of the disease [ 4 ], the administration or not of Interferon (IFN)-beta-1a [ 5 ], the presence of particular MS-risk polymorphism [ 6 ] or focusing on the redox status of the cells [ 7 ]. Eventually, although mitochondrial dysfunction is not only a central event in many pathologies, it contributes to age-related processes.…”
Section: Introductionmentioning
confidence: 99%
“…The association of the rs3738067 A>G with YTHDF2 expression was determined in the GTEx portal via eQTLs analysis. The integrative analyses of eQTL and SNP information may provide more understanding about the complex disease-modulating network ( 30 ). However, further studies are needed to substantiate the association between the rs3738067 A>G polymorphism and mRNA expression levels of YTHDF2 .…”
Section: Discussionmentioning
confidence: 99%